Kesulitan Guru dalam Melaksanakan Pembelajaran Matematika dengan Kurikulum 2013 Masa Pandemi Covid-19 - Firda Devianti Komalasari; I Ketut Widada; Husniati Husniati (Journal of Classroom Action Research, 2022)
This research discusses the difficulties of teachers in carrying out mathematics learning with the 2013 Curriculum during the Covid-19 Pandemic in SDN Cluster 1 Sumbawa. The purpose of this study is to find out the difficulties experienced by teachers and find out how much difficulty teachers face in carrying out math learning with the 2013 curriculum during the Covid-19 Pandemic in SDN Cluster I Sumbawa. This research is quantitative research with a descriptive approach, while data collection is done by questionnaire and documentation. Research found that there are difficulties experienced by teachers in the implementation of mathematics learning during Covid-19, the difficulties experienced by teachers are as follows; (a) plan learning, (b) the implementation of learning, (c) evaluation of learning. The level of problems experienced by teachers in carrying out math learning during the Covid-19 pandemic is teachers who have high category difficulties as many as 3 teachers with a percentage of 21.43%, teachers who have moderate category difficulties as many as 8 teachers with a percentage of 57.14%, and teachers who have low category difficulties as many as 3 teachers with a percentage of 21.43%.